Preparation method and application of sodium vanadium phosphate positive electrode material

By mixing the phosphorus source, sodium source and vanadium source and grinding and sintering, a simple operation and low cost sodium vanadyl phosphate positive electrode material is prepared, which solves the problems of complex and high cost in the prior art preparation method. The recycling of used battery resources has been realized.

CN116395654BActive Publication Date: 2025-02-25HUNAN SHUNHUA LITHIUM IND CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310187633.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-01
Publication Date
2025-02-25
Estimated Expiration
2043-03-01

AI Technical Summary

Technical Problem

The existing preparation method of the positive electrode material of sodium ion battery has problems such as complex operation, high cost and long cycle, and it is difficult to realize the recycling of the phosphorus and sodium sources after recycling and processing of waste lithium iron phosphate batteries.

Method used

A simple method is used to mix the phosphorus source, sodium source and vanadium source and grind it, add the carbon source and then sieved and dried. Finally, the sodium vanadyl phosphate positive electrode material is prepared by the temperature system of two stages of sintering.

Benefits of technology

The preparation of sodium vanadyl phosphate positive electrode material with simple operation, low cost and short cycle is realized, and the phosphorus and sodium sources in waste lithium iron phosphate batteries can be effectively utilized to reduce waste and improve economic and environmental protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116395654B_ABST
    Figure CN116395654B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a sodium vanadium phosphate positive electrode material and its application in preparing a sodium positive electrode material. The preparation method comprises the following steps: mixing and grinding a phosphorus source, a sodium source, and a vanadium source to obtain a ground mixture A; mixing a carbon source and continuing to grind to obtain a ground mixture B; sieving the mixture B, adding an abrasive to rinse, drying and grinding the obtained suspension of a mixed precursor and an abrasive to obtain a precursor powder; sintering the obtained precursor powder to obtain a sodium vanadium phosphate positive electrode material. The method of the present invention is simple to operate and low in cost, and can realize the recycling of phosphorus sources after recycling and processing of waste lithium batteries, generating less waste, being economical and environmentally friendly. The preparation method of the present invention is more direct, convenient, safe, and low-cost. After ball milling, sintering can perfectly realize the preparation of sodium vanadium phosphate by adjusting the amount of carbon source added and the inert gas filling time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy sodium ion battery positive electrode materials, and in particular to a method for preparing sodium vanadium phosphate. Background Art

[0002] Driven by the huge demand in the new energy market, with the widespread use of lithium salts, especially after entering the transportation industry market, the various consumption of lithium and lithium-based chemicals has led to a sharp rise in the price of lithium. At the same time, in terms of reserves, lithium cannot simultaneously meet the growing industrial development needs of transportation and power grid applications, which has also caused people to worry deeply about future tensions. On this basis, cheap sodium is everywhere, because sodium with extremely high abundance brings price advantages and has been applied to battery systems, and the physical and chemical properties of sodium and lithium are similar. Sodium-based electrochemical energy storage has a huge application market in large-scale energy storage and power grid development.

[0003] At present, sodium-ion cathode materials with industrial prospects can be divided into three types: layered metal oxides, polyanionic materials and Prussian blue derivatives. Other companies have developed and produced sodium-ion batteries, such as HiNa's P2 and O3 copper-iron-manganese layered oxide cathode materials, Faradion's O3 / P2 mixed nickel-manganese-magnesium-titanium layered oxide cathode materials, Aquion Energy's manganese-based oxide AHI batteries, and Novasis Energy's PBA cathode materials, all of which have achieved comparable specific capacity and energy retention. HiNa successfully installed the world's first 30 kW / 100 kW•h SIB energy storage system in 2019.

[0004] Layered metal oxide cathode materials: Na + The phase change during the intercalation and delamination process leads to unstable unit cells and easy structural collapse, which means that the cycle life of the material is not ideal and the specific capacity degrades rapidly. However, its high energy density and high voltage platform make it a research hotspot in recent years. Researchers use inactive metal ions such as Al 3+ etc. as the support of the layered structure to ensure the stability of the structure.

[0005] Prussian blue derivatives are a very suitable cathode material for sodium ion batteries from the perspective of electrochemical performance. However, CN is used in the preparation process. - It will pollute the environment and form highly toxic HCN when it comes into contact with acid, which limits its practical application.

[0006] Polyanion positive electrode materials: Since the polyanion group has an inductive effect and a relatively stable structure, this type of compound exhibits a higher working potential, and the phosphate group therein has a unique stable structure that exhibits excellent rate performance and cycle stability during the cycle process.

[0007] Although two-dimensional layered oxides can expand the space between MO2 layers to accommodate larger Na + , but Na + -Na + Coulomb interaction and Na + Preferring to occupy triangular prisms rather than octahedral oxidation points, as Na + The deintercalation leads to a series of phase transitions. The theoretical specific capacity of NaVOPO4 reaches 145 mAh / g. The skeleton of monoclinic NaVOPO4 consists of VO6 octahedral chains with shared angles parallel to the C axis, which are connected by PO4 tetrahedrons. The VO6 octahedron is formed by alternating 4 equatorial VO bonds and two axial VO bonds along the chain, which has the characteristics of forming vanadium-based bonds introduced into the ferroelectric chain. This framework provides Na along the

[110] , [-110] and

[101] axes. + Three-dimensional channel of migration. PO4 3- The action of polyanions increases the voltage of transition metal redox to a voltage higher than that of oxides. The skeleton of monoclinic NaVOPO4 consists of shared angle VO6 octahedral chains parallel to the C axis, which are connected by PO4 tetrahedrons. Compared with oxide and layered compound systems, polyanion materials show high thermal stability and have potential for high cyclability and safety. They are supported by covalent bonds such as P and O. The framework structure, especially the positive electrode is in a deep oxidation state, and the phosphate group can obtain a higher voltage. In addition, the phosphate group reduces the difficulty of oxygen release when fully charged, thereby increasing the safety of the battery.

[0008] The invention with patent number CN112010276B adopts spray drying, and the spray drying equipment is complex and the control conditions are not easy; for example, the invention with patent number CN108134082A adopts multiple pretreatment sintering, and the multiple sintering time, the combustion cost is higher, and the test cycle is long; the invention with patent number CN115312747A adopts hydrothermal method to prepare precursor, and the pretreatment time of hydrothermal method is long. Therefore, it is very important to provide a method for preparing positive electrode materials with simple operation, low cost and short cycle. Summary of the invention

[0009] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology, and provide a method for preparing a sodium vanadium phosphate positive electrode material with simple operation, low cost, uniform particles of the prepared sodium vanadium phosphate positive electrode material, and stable phase between batches, thereby realizing the recycling of phosphorus source and sodium source after the recycling of waste lithium iron phosphate batteries.

[0010] In order to solve the above technical problems, the technical solution proposed by the present invention is:

[0011] A method for preparing a sodium vanadium phosphate positive electrode material comprises the following steps:

[0012] (1) A phosphorus source, a sodium source, and a vanadium source are mixed and ground to obtain a ground mixture A.

[0013] (2) Mixing the carbon source with the vanadium source in the mixture A obtained in step (1), and continuing to grind to obtain a ground mixture B.

[0014] (3) The mixture B obtained in step (2) is sieved, and an abrasive is added to rinse to obtain a suspension of the mixed precursor and the abrasive.

[0015] (4) Drying and grinding the suspension of the mixed precursor and the abrasive obtained in step (3) to obtain a precursor powder.

[0016] (5) Sintering the precursor powder obtained in step (4) to obtain a sodium vanadium phosphate positive electrode material.

[0017] Preferably, the phosphorus source, sodium source and vanadium source in step (1) are mixed in a molar ratio of 1:1:1, the phosphorus source and sodium source are sodium phosphate, and the vanadium source is a combination of one or more of ammonium metavanadate, vanadium pentoxide, vanadium dioxide and vanadium trioxide.

[0018] Preferably, the carbon source in step (2) is mixed with the vanadium source in the mixture A obtained in step (1) in a molar ratio of 1: (0.05-0.12).

[0019] Preferably, the carbon source in step (2) is a combination of one or more of oxalic acid, citric acid, salicylic acid, glucose, malic acid, and activated carbon. The main purpose of the carbon source is to reduce the +5-valent vanadium in ammonium metavanadate, and the vanadium in sodium vanadate phosphate is +4-valent, which requires a reducing agent for reduction. The reason for choosing a carbon source is that even if an excess of carbon source is added, it will not be burned out and remain in the sample during the sintering process, and it will not affect the quality of sodium vanadate phosphate. The amorphous carbon produced after sintering can not only improve the conductivity of the positive electrode material, but also needs to be mixed with the carbon material in the process of preparing the battery to obtain a composite material and then coated on the electrode. The carbon source will not affect the subsequent performance.

[0020] Preferably, the grinding in step (1) and step (2) is ball milling; the grinding medium of the ball milling is a zirconium ball of 0.3-4.0 mm; the ball mill used for the ball milling is a combination of one or more of a planetary ball mill and a sand mill, and the rotation speed is 200-800 rpm.

[0021] Preferably, the ball-to-material ratio in step (1) is (1.0-10.0):1, and the ball milling time is 10-120 min.

[0022] Preferably, the ball-to-material ratio in step (2) is (1.0-10.0):1, and the ball milling time is 0.5-6h.

[0023] Preferably, the grinding agent in step (3) is a combination of one or more of acetone, anhydrous ethanol, propanol, and ether; the drying in step (4) is performed in a vacuum drying oven, the drying temperature is 50-80°C, and the drying time is 2-24h; the grinding in step (4) is performed by grinding with a mortar. In the grinding stage, the grinding agent plays a role in aiding grinding, which can improve the efficiency of ball milling, make the mixing more uniform, and the particle size more delicate, which is conducive to the subsequent redox reaction; at the same time, the grinding agent in the ball mill can isolate part of the air and reduce the occupation of oxygen in the air to citric acid, thereby improving the reduction efficiency of citric acid to +5 valent vanadium in ammonium metavanadate, which can not only improve the purity of sodium vanadium phosphate in the sample but also reduce the amount of citric acid used, saving costs.

[0024] Preferably, the sintering in step (5) is a two-stage sintering.

[0025] Preferably, the specific operation of the two-stage sintering is: during the first stage of sintering, the heating rate of sintering is 1-20℃ / min, the temperature is raised to 200-450℃ and kept for 1-6h, and an inert gas is introduced for the second stage of sintering; during the second stage of sintering, the heating rate of sintering is 1-20℃ / min, the temperature is raised to 600-900℃ and kept for 5-10h, and finally cooled to room temperature. Ball milling, drying and heat preservation and the first stage of sintering actually undergo redox reactions, and the +5-valent vanadium is reduced to +4-valent vanadium. The first stage is different, such as the inert gas needs high temperature to consume the excess carbon source by oxygen or be reduced to amorphous carbon by high temperature; and the second stage is filled with inert gas mainly to protect the +4-valent vanadium from being oxidized during the crystallization annealing process, and to improve the purity and yield of sodium vanadium oxyphosphate.

[0026] Based on the overall inventive concept, the present invention also provides an application of a sodium vanadium phosphate positive electrode material, wherein the sodium vanadium phosphate positive electrode material is used to prepare a sodium battery positive electrode material.

[0027] The implementation principle of the present invention is as follows:

[0028] In step (5) of the method of the present invention, the preparation of sodium vanadium phosphate positive electrode material is achieved by a two-stage sintering temperature system. First, during the drying and first stage 200-450°C process, a redox reaction occurs, and pentavalent vanadium is reduced to tetravalent vanadium. The chemical equation is as follows:

[0029] 18NaH2PO4+18NH4VO3+C6H8O7→18NaVOPO4+6CO2↑+18NH3↑+31H2O↑

[0030] Then, during the second annealing process at 600-900°C, the sodium vanadium phosphate positive electrode material is crystallized.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. The method of the present invention is simple to operate and low in cost. It can realize the recycling of phosphorus source after recycling of waste lithium batteries, generate less waste, and is economical and environmentally friendly. The preparation method of the present invention is more direct, convenient, safe, and low-cost. After ball milling, sintering can be performed. By adjusting the amount of carbon source added and the inert gas filling time, the preparation of sodium vanadate phosphate can be perfectly realized.

[0033] 2. The present invention synthesizes a positive electrode material for polyanion sodium ion batteries with a simple process. The preparation process is simple, controllable, safe, low in production cost, and has little environmental pollution. The prepared sodium vanadium phosphate has uniform particles and stable phase, which provides a positive electrode material for the next step of preparing safer and more environmentally friendly low-cost sodium ion batteries. It can be applied to the field of new energy batteries to prepare safer and low-cost sodium battery positive electrode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0035] Figure 1 It is the XRD pattern of some embodiments and comparative examples of NaVOPO4 compared with the standard card PDF#76-0417. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.

[0037] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0038] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0039] Embodiment 1:

[0040] A method for preparing sodium vanadium phosphate positive electrode material, comprising: first measuring an appropriate amount of anhydrous ethanol and pouring it into a ball mill, weighing sodium dihydrogen phosphate dihydrate and ammonium metavanadate in a molar ratio of 1:1:1 and pouring them into the ball mill, weighing 2.5 times of 0.6-0.8 mm zirconium balls in a ratio of 1:2.5, and then adding an appropriate amount of anhydrous ethanol to ensure that the anhydrous ethanol covers the mixture of powder and zirconium balls. Subsequently, ball milling is performed at 400 rpm in a planetary ball mill for 30 minutes, monohydrated citric acid is weighed and added in a ratio of 1:0.06, and ball milling is continued at 400 rpm in the planetary ball mill for 2 hours, the zirconium balls are separated through a 50-mesh sieve, and then rinsed with a small amount of anhydrous ethanol and poured into a culture dish to obtain a suspension of a mixed precursor and anhydrous ethanol, which is moved to a 60°C vacuum drying oven for drying for 8 hours, and taken out and ground to obtain a precursor powder. The precursor was transferred to a combustion boat and placed in a tube furnace. The temperature was first raised to 350°C at a heating rate of 5°C / min under natural conditions and kept at this temperature for 4 hours. Then, an inert gas was introduced and the temperature was raised to 750°C at the same heating rate and kept at this temperature for 8 hours. Finally, the precursor was naturally cooled to room temperature under the protection of an inert gas and taken out to obtain sodium vanadium phosphate. The XRD pattern compared with the standard card PDF#76-0417 is shown in FIG. Figure 1 As shown, the sample XRD matches the sodium vanadium phosphate standard card PDF#76-0417, with good crystallinity and no impurity phase.

[0041] An application of a sodium vanadium phosphate positive electrode material, wherein the sodium vanadium phosphate positive electrode material is used to prepare a sodium battery positive electrode material.

[0042] Embodiment 2:

[0043] A method for preparing sodium vanadium phosphate positive electrode material comprises: firstly measuring an appropriate amount of anhydrous ethanol and pouring it into a ball mill, weighing sodium dihydrogen phosphate dihydrate and ammonium metavanadate in a molar ratio of 1:1:1 and pouring them into the ball mill, weighing 3 times of 0.6-0.8 mm zirconium balls in a ratio of 1:3, and then adding an appropriate amount of anhydrous ethanol to ensure that the anhydrous ethanol covers the mixture of powder and zirconium balls. Subsequently, ball milling is performed at 450 rpm in a planetary ball mill for 40 minutes, monohydrated citric acid is weighed and added in a molar ratio of 1:0.07, and ball milling is continued at 450 rpm in the planetary ball mill for 2.5 hours, the zirconium balls are separated through a 50 mesh sieve, and then rinsed with a small amount of anhydrous ethanol and poured into a culture dish to obtain a suspension of a mixed precursor and anhydrous ethanol, which is moved to a 65°C vacuum drying oven for drying for 9 hours, and taken out and ground to obtain a precursor powder. The precursor was transferred to a combustion boat and placed in a tube furnace. The temperature was first raised to 380°C at a heating rate of 4°C / min under natural conditions and kept at this temperature for 5 hours. Then, an inert gas was introduced and the temperature was raised to 800°C at the same heating rate and kept at this temperature for 9 hours. Finally, the precursor was naturally cooled to room temperature under the protection of an inert gas and taken out to obtain sodium vanadium phosphate. The XRD pattern compared with the standard card PDF#76-0417 is shown in FIG. Figure 1 As shown, the sample XRD matches the sodium vanadium phosphate standard card PDF#76-0417 and contains no impurities.

[0044] Embodiment 3:

[0045] A method for preparing sodium vanadium phosphate positive electrode material comprises: firstly measuring an appropriate amount of anhydrous ethanol and pouring it into a ball mill, weighing sodium dihydrogen phosphate dihydrate and ammonium metavanadate in a molar ratio of 1:1:1 and pouring them into the ball mill, weighing 3.5 times of 0.6-0.8 mm zirconium balls in a ratio of 1:3.5, and then adding an appropriate amount of anhydrous ethanol to ensure that the anhydrous ethanol covers the mixture of powder and zirconium balls. Subsequently, ball milling is performed at 500 rpm in a planetary ball mill for 35 minutes, monohydrated citric acid is weighed and added in a ratio of 1:0.08, and ball milling is continued at 500 rpm in the planetary ball mill for 3 hours, the zirconium balls are separated through a 50 mesh sieve, and then rinsed with a small amount of anhydrous ethanol and poured into a culture dish to obtain a suspension of a mixed precursor and anhydrous ethanol, which is moved to a 70°C vacuum drying oven for drying for 16 hours, and taken out and ground to obtain a precursor powder. The precursor was transferred to a combustion boat and placed in a tubular furnace. The temperature was first increased to 400°C at a heating rate of 6°C / min under natural conditions and kept warm for 6 hours. An inert gas was then introduced and the temperature was increased to 700°C at the same heating rate and kept warm for 8.5 hours. Finally, the precursor was naturally cooled to room temperature under the protection of an inert gas and taken out to obtain sodium vanadium phosphate.

[0046] Embodiment 4:

[0047] A method for preparing sodium vanadium phosphate positive electrode material comprises: firstly measuring an appropriate amount of anhydrous ethanol and pouring it into a ball mill, weighing sodium dihydrogen phosphate dihydrate and ammonium metavanadate in a molar ratio of 1:1:1 and pouring them into the ball mill, weighing 4 times of 0.6-0.8 mm zirconium balls in a ratio of 1:4, and then adding an appropriate amount of anhydrous ethanol to ensure that the anhydrous ethanol covers the mixture of powder and zirconium balls. Subsequently, ball milling is performed at 350 rpm in a planetary ball mill for 60 minutes, monohydrated citric acid is weighed and added in a ratio of 1:0.09, and ball milling is continued at 350 rpm in the planetary ball mill for 4 hours, the zirconium balls are separated through a 50 mesh sieve, and then rinsed with a small amount of anhydrous ethanol and poured into a culture dish to obtain a suspension of a mixed precursor and anhydrous ethanol, which is moved to a 75°C vacuum drying oven for drying for 20 hours, and taken out and ground to obtain a precursor powder. The precursor was transferred to a combustion boat and placed in a tubular furnace. The temperature was first increased to 420°C at a heating rate of 3°C / min under natural conditions and kept warm for 4 hours. An inert gas was then introduced and the temperature was increased to 720°C at the same heating rate and kept warm for 5 hours. Finally, the precursor was naturally cooled to room temperature under the protection of an inert gas and taken out to obtain sodium vanadium phosphate.

[0048] Comparative Example 1:

[0049] A method for preparing sodium vanadium phosphate positive electrode material comprises: firstly measuring an appropriate amount of anhydrous ethanol and pouring it into a ball mill, weighing sodium dihydrogen phosphate dihydrate and ammonium metavanadate in a molar ratio of 1:1:1 and pouring them into the ball mill, weighing 2.0 times of 0.6-0.8 mm zirconium balls in a ratio of 1:2.0, and then adding an appropriate amount of anhydrous ethanol to ensure that the anhydrous ethanol covers the mixture of powder and zirconium balls. Subsequently, ball milling is performed at 430 rpm in a planetary ball mill for 25 minutes, monohydrated citric acid is weighed and added in a ratio of 1:0.08, and ball milling is continued at 430 rpm in the planetary ball mill for 3.5 hours, the zirconium balls are separated through a 50 mesh sieve, and then rinsed with a small amount of anhydrous ethanol and poured into a culture dish to obtain a suspension of a mixed precursor and anhydrous ethanol, which is moved to a 68°C vacuum drying oven for drying for 12 hours, and taken out and ground to obtain a precursor powder. The precursor was transferred to a combustion boat and placed in a tube furnace. The temperature was first raised to 390°C at a heating rate of 4°C / min under natural conditions and kept at that temperature for 4 hours. Then, an inert gas was introduced and the temperature was raised to 690°C at the same heating rate and kept at that temperature for 6 hours. Finally, the precursor was naturally cooled to room temperature under the protection of an inert gas and taken out to obtain sodium vanadium phosphate. The XRD pattern compared with the standard card PDF#76-0417 is shown in FIG. Figure 1 As shown, the sample XRD matches the sodium vanadium phosphate standard card PDF#76-0417, has no impurity phase, and the diffraction peak intensity is slightly weaker than that of Example 1, indicating that Example 1 has stronger crystallinity.

[0050] Comparative Example 2:

[0051] A method for preparing sodium vanadium phosphate positive electrode material comprises: firstly measuring an appropriate amount of anhydrous ethanol and pouring it into a ball mill, weighing sodium dihydrogen phosphate dihydrate and ammonium metavanadate in a molar ratio of 1:1:1 and pouring them into the ball mill, weighing 4.5 times of 0.6-0.8 mm zirconium balls in a ratio of 1:4.5, and then adding an appropriate amount of anhydrous ethanol to ensure that the anhydrous ethanol covers the mixture of powder and zirconium balls. Subsequently, ball milling is performed at 460 rpm in a planetary ball mill for 45 minutes, monohydrated citric acid is weighed and added in a ratio of 1:0.10, and ball milling is continued at 520 rpm in the planetary ball mill for 1.5 hours, the zirconium balls are separated through a 50-mesh sieve, and then rinsed with a small amount of anhydrous ethanol and poured into a culture dish to obtain a suspension of a mixed precursor and anhydrous ethanol, which is moved to a 72°C vacuum drying oven for drying for 13 hours, and taken out and ground to obtain a precursor powder. The precursor was transferred to a combustion boat and placed in a tubular furnace. The temperature was first increased to 350°C at a heating rate of 5°C / min under natural conditions and kept at this temperature for 4 hours. An inert gas was then introduced and the temperature was increased to 750°C at the same heating rate and kept at this temperature for 8 hours. Finally, the precursor was naturally cooled to room temperature under the protection of an inert gas and taken out to obtain sodium vanadium phosphate.

Claims

1. A method for preparing a sodium vanadium phosphate positive electrode material, characterized in that: The steps include: (1) mixing and grinding a phosphorus source, a sodium source, and a vanadium source to obtain a ground mixture A; (2) mixing the carbon source with the mixture A obtained in step (1), and continuing to grind to obtain a ground mixture B; (3) sieving the mixture B obtained in step (2), adding an abrasive to rinse, and obtaining a suspension of the mixed precursor and the abrasive; the abrasive is a combination of one or more of acetone, anhydrous ethanol, propanol, and ether; (4) drying and grinding the suspension of the mixed precursor and the abrasive obtained in step (3) to obtain a precursor powder; (5) Sintering the precursor powder obtained in step (4), wherein the sintering is performed in two stages, and the specific operation of the two stages is as follows: during the first stage sintering, the sintering heating rate is 1-20°C / min, the temperature is raised to 200-450°C and kept for 1-6 hours, and an inert gas is introduced for the second stage sintering; during the second stage sintering, the sintering heating rate is 1-20°C / min, the temperature is raised to 600-900°C and kept for 5-10 hours, and finally the temperature is lowered to room temperature to obtain the sodium vanadium phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: In step (1), the phosphorus source, sodium source and vanadium source are mixed in a molar ratio of 1:1:1, the phosphorus source and sodium source are sodium phosphate, and the vanadium source is a combination of one or more of ammonium metavanadate, vanadium pentoxide, vanadium dioxide and vanadium trioxide.

3. The preparation method according to claim 1, characterized in that: The carbon source in step (2) is mixed with the vanadium source in the mixture A obtained in step (1) in a molar ratio of 1: (0.05-0.12).

4. The preparation method according to claim 1, characterized in that: The carbon source in step (2) is a combination of one or more of oxalic acid, citric acid, salicylic acid, glucose, malic acid and activated carbon.

5. The preparation method according to claim 1, characterized in that: The grinding in step (1) and step (2) is ball milling; the grinding medium of the ball milling is a zirconium ball of 0.3-4.0 mm; the ball mill used in the ball milling is a combination of one or more of a planetary ball mill and a sand mill, and the rotation speed is 200-800 rpm.

6. The preparation method according to claim 5, characterized in that: The ball-to-material ratio of the grinding in step (1) is (1.0-10.0):1, and the ball-milling time is 10-120 min.

7. The preparation method according to claim 5, characterized in that: The ball-to-material ratio of the grinding in step (2) is (1.0-10.0):1, and the ball milling time is 0.5-6h.

8. The preparation method according to claim 1, characterized in that: The drying in step (4) is performed by using a vacuum drying oven, the drying temperature is 50-80° C., and the drying time is 2-24 hours; the grinding in step (4) is performed by using a mortar.

Citation Information

Patent Citations

  • Na3V2(PO4)3 cathode material for sodium-ion battery as well as preparation and application of cathode material

    CN108134082A

  • A method for preparing sodium vanadium fluorophosphate cathode material for sodium-ion batteries

    CN112010276B

  • Nano-carbon material composite single crystal sodium vanadyl fluorophosphate material and preparation method and application of nano-carbon material composite single crystal sodium vanadyl fluorophosphate material

    CN115312747A

  • Preparation method of vanadium sodium fluophosphate cathode material of hybrid ion battery

    CN102306771A

  • Preparation method of sodium vanadyl phosphate / graphene composite material

    CN104078676A